An Information Framing Through Newspaper Media: Knowledge Transfer on Children - Febriyanto, Febriyanto; Sadikin, Mohammad Aufar (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2020)
The Kompas newspaper is known as a daily for adults, but there is a rubric aimed at children called the Kompas Anak rubric. it is important to see how the framing, starting from the knowledge, information, messages, illustrations or drawings, writing, words and sentences that differ between children and adults. This study examines the transfer of knowledge through the "Kompas Anak" rubric. The purpose of this study is to describe the process of knowledge transfer to the child through mass media in the form of rubric named "Kompas Anak" by looking at the framing done on articles that containing knowledge for children. This qualitative research uses framing analysis method. Framing method is used to analyze knowledge transfer by the sender of knowledge through the rubric of "Kompas Anak". The results showed that the process of knowledge transfer that occurs in the "Kompas Anak" rubric is a mean to instill general knowledge in accordance with the understanding of children, so they can capture the knowledge transferred by the sender of knowledge.